Surface strain-hardening of the blades of gas-turbine engines in an ultrasonic field - Yatsenko, V.K.; Stebel'kov, I.A.; Pritchenko, V.F. (Проблемы прочности, 1985)
The completed tests convincingly show that the time of strain-hardening of small blades of alloy VT8 by 1.3-mm-diam. balls should be no greater than 5 min if the edges are not protected by shields. Such strain-hardening significantly increases the endurance limits of blades with almost no reduction in their resistance to impact loads.